The Contradictory Position of Francophone Minority Communities in the Canadian Colonial Order - Melançon, Jérôme (Journal of the Canadian Association for Curriculum Studies, 2023)
Francophone communities in minority situations find themselves in a contradictory situation of benefiting from settler colonialism, while at the same time having to fight for recognition promised in the constitutional order. Contrary to the way in which Francophones tend to represent their communities- namely, as a continuation of a French-Canadian nation said to be colonized – their rights and the idea of Canadian duality are rooted both in a French colonial project that continues within British and Canadian colonialism, and in the appropriation of territory and the erasure of this appropriation. The Truth and Reconciliation Commission’s Calls to Action of the Truth and the National Inquiry into Missing and Murdered Indigenous Women and Girls’ Calls to Justice – and, more generally, the relations to be created and maintained with Indigenous peoples – will therefore take on a meaning that stems from these contradictions. This article explains the challenge of understanding Francophone communities’ participation in colonialism through their relationship to territory, state, means of social reproduction, and traditions and practices. Finally, it identifies some of the responsibilities arising from the role played by Francophone communities in the colonial order.